Overview of rapid molecular test (RMT)–gene xpert mtb/rif ultra results in pulmonary tuberculosis patients based on the history of therapy - Balada A Nurinsani; Susanti Ratunanda (ACTA Medical Health Sciences, 2024)
Tuberculosis (TB) is a health threat that remains a problem both globally and nationally. Indonesia has the world’s second highest number of TB cases. Various examination methods were developed for detecting this disease; one of the most developed is the Rapid Molecular Test (RMT). This study aims to describe the results of a rapid molecular test (GeneXpert) using the Xpert MTB/RIF Ultra tool in pulmonary tuberculosis based on a treatment history consisting of new cases, relapse cases, and drug withdrawal cases. The study subjects were 47 patients with pulmonary tuberculosis at Puskesmas Ciwidey, Bandung Regency Health Office, from February to September 2023. The results showed that characteristics of respondents were male (57.4%), female (42.6%), and mostly were aged between 20 and 44 years (53.1%). These results are in line with previous research. The majority of cases (87.2%) were new cases and the most RMT examination results indicated that MTB detected rifampicin sensitivity (78.7%). In new cases, MTB-detected rifampicin sensitivity at 78.1%, MTB-not detected at 19.5%, and MTB-detected rifampicin resistance at 2.4%. In relapse cases, all respondents (100%) showed MTB detected to be rifampicin-sensitive. In drug withdrawal cases, MTB detected 75% rifampicin sensitivity and 25% rifampicin resistance. The results of this study indicate that one possible factor in the occurrence of germ resistance to antituberculosis drugs is inadequate treatment of TB patients, in this case drug withdrawal cases. DOI : 10.35990/amhs.v3n1.p31-39 REFERENCES Kementerian Kesehatan Republik Indonesia. Tuberkulosis Paru. Pedoman Nasional Pelayanan Kedokteran Tatalaksana Tuberkulosis. 2020; p10–26. World Health Organization. Tuberculosis Incidence. [Internet]. Available from: https://www.who.int/teams/global-tuberculosis-programme/tb-reports/global-tuberculosis-report-2022/tb-disease-burden/2-1-tb-incidence Kementerian Kesehatan Republik Indonesia. Petunjuk Teknis Pemeriksaan TB Menggunakan Tes Cepat Molekular. 2017; p4–126. Shapiro AE, Ross JM, Yao M, Schiller I, Kohli M, Dendukuri N, et al. Xpert MTB/RIF and Xpert Ultra assays for screening for pulmonary tuberculosis and rifampicin resistance in adults, irrespective of signs or symptoms. Cochrane Database Syst Rev. 2021;3:1–82. doi:10.1002/14651858.CD013694.pub2 Kementerian Kesehatan Republik Indonesia. Pedoman Nasional Pelayanan Kedokteran Tatalaksana Tuberkulosis. 2019; p9–23. Dorman SE, Schumacher SG, Alland D, Nabeta P, Armstrong DT, King B, et al. Xpert MTB/RIF Ultra for detection of Mycobacterium tuberculosis and rifampicin resistance: a prospective multicentre diagnostic accuracy study. Lancet Infect Dis. 2018;18(1):76–84. doi:10.1016/S1473-3099(17)30691-6 World Health Organization. Systematic Screening for Tuberculosis Disease. WHO Consolidated Guidelines for Tuberculosis. 2021; p5–35. Badan Penelitian dan Pengembangan Kesehatan. Laporan Nasional RISKESDAS 2018: Tuberkulosis. 2018; p80. Hartiyah L, Rahmiayti, Santoyo D. Gambaran hasil pemeriksaan tes cepat molekuler Mycobacterium tuberculosis di RSUD Ulin Banjarmasin tahun 2020–2021. 2023;6:69–76. Chinwong D, Mookmanee N, Chongpornchai J, Chinwong S. A comparison of gender differences in smoking behaviors, intention to quit, and nicotine dependence among Thai university students. J Addict. 2018;2018:1–8. doi:10.1155/2018/8081670 Kementerian Kesehatan Republik Indonesia. Rencana Aksi Nasional Kelompok Lanjut Usia. 2016; p22. World Health Organization. Global Tuberculosis Report 2022. 2022; p5–33. Peraturan Presiden Republik Indonesia. Penanggulangan Tuberkulosis. 2021; p2–26. Myneedu VP, Behera D, Verma AK, Bhalla M, Singh N, Arora J, et al. Xpert MTB/RIF assay for tuberculosis diagnosis: Evaluation in an Indian setting. Int J Tuberc Lung Dis. 2014;18(8):958–60. doi:10.5588/ijtld.13.0328 Zhang M, Xue M, He JQ. Diagnostic accuracy of the new Xpert MTB/RIF Ultra for tuberculosis disease: A preliminary systematic review and meta-analysis. Int J Infect Dis. 2020;90:35–45. doi:10.1016/j.ijid.2019.09.016 Bisognin F, Lombardi G, Lombardo D, Carla Re M, Dal Monte P. Improvement of Mycobacterium tuberculosis detection by Xpert MTB/RIF Ultra: A head-to-head comparison on Xpert-negative samples. PLoS One. 2018;13(8):1–7. doi:10.1371/journal.pone.0201934 Biswas S, Uddin MKM, Paul KK, Ather MF, Ahmed S, Nasrin R, et al. Xpert MTB/RIF Ultra assay for detection of Mycobacterium tuberculosis in people with negative conventional Xpert MTB/RIF but chest imaging suggestive of tuberculosis in Dhaka, Bangladesh. Int J Infect Dis. 2022;114:51–244. doi:10.1016/j.ijid.2021.11.010 Theron G, Venter R, Calligaro G, Smith L, Limberis J, Meldau R, et al. Xpert MTB/RIF results in patients with previous tuberculosis: Can we distinguish true from false positive results? Clin Infect Dis. 2016;62(8):995–1001. doi:10.1093/cid/civ1223 Horne DJ, Kohli M, Zifodya JS, Schiller I, Dendukuri N, Tollefson D, et al. Xpert MTB/RIF and Xpert MTB/RIF Ultra for pulmonary tuberculosis and rifampicin resistance in adults. Cochrane Database Syst Rev. 2019;6:7–11. doi:10.1002/14651858.cd009593.pub4 Kementerian Kesehatan Republik Indonesia. Petunjuk Teknis Penatalaksanaan Tuberkulosis Resisten Obat di Indonesia. 2020; p26–69.